Longterm follow up of Deep Brain Stimulation versus Lesioning in the treatment of Parkinson’s Disease: A single center study - Shrestha, Resha; Gurung, Pritam; Shrestha, Pranaya; Rajbhandari, Pravesh; Dhakal, Sudan; Acharya, Samir; Dahal, Rizu; Dhamala, Januka; Dhungel, Raju; Takaomi, Taira; et al. (Nepal Journal of Neuroscience, 2025)
Introduction: Parkinson’s disease (PD) is a neurodegenerative disorder characterized primarily by loss of dopamine neurons in the Substantia Nigra Pars compacta resulting in various symptoms like bradykinesia, rigidity and tremor. Surgical treatments like lesioning procedure (Pallidotomy) and Deep brain stimulation surgery are well established surgical treatment for drug resistant PD Materials & Methods: All the patients who underwent surgical treatment of Parkinsons Disease in Annapurna Neurological Institute And allied Sciences from 2016 January to December 2022 have been included in this study. Patients undergoing DBS versus lesioning in the treatment of Parkinson disease with more than two years follow up were reviewed retrospectively. Results: Eighty cases were included in this study with 50 cases of Pallidotomy and 30 cases of DBS. The male to female ratio was 2:1 in both groups. There was no difference in mean duration of illness. However, the surgical timing, hospital stay and frequency of follow ups and surgical expenses were more in DBS group. Mean change in Unified Parkinsons Disease Rating Score (UPDRS) III at the immediately after surgery was 70 percent in Pallidotomy group and 65 % in DBS group(P=0.4). However it was not statistically significant. In long term follow up period after two years, we found that the mean change in off period of UPDRS score in Lesioning vs DBS was 46.6 % vs 46.5% .(p=0.8) There was only 10 percent reduction on the dose of dopamine in pallidotomy group whereas there was 30 percent reduction in DBS group. Similarly there was significant reduction in Dyskinesia both in Pallidotomy and DBS group. Conclusion: Both lesioning and DBS procedures are equally effective surgical treatment of Parkinsons Disease. Lesioning procedure are more feasible in our context due to its cost effectiveness and long term benefit.